Passenger Name Record Data Protection under European Union and United States Agreement: Security over Privacy? - Rizaldy Anggriawan; Andi Agus Salim; Yordan Gunawan; Mohammad Hazyar Arumbinang (Faculty of Law, Hasanuddin University, 2022)
Privacy should become a key component in the IT system. It is not something to be considered at last but from the very early stages. Almost no nation has a greater sense of personal data security which could be equivalent to the European level. Since 9/11, the United States has declared to utilize PNR as a method for combating terrorism by associating PNR data with criminal records. Nevertheless, in fact, the majority of data found in the PNR is immense and most of this data is of a confidential nature. The paper used doctrinal legal research methodology utilizing the case and comparative law approach. It elaborates particular cases in relation to data protection issues. It also explores the differences between EU and US law which hinder the idea of data protection in particular on PNR. The study revealed that security is one of the most critical issues which hinder the agreement between the EU and the US on PNR data protection. As the EU promotes the highest standard to the data protection referring to the European community history and GDPR provisions, while the US places national security as a main priority beyond the privacy issues.